Overview of Mothers' Knowledge and Education Regarding Immunization - Andrianto, Muhammad Bagus; Padila, Padila; Andri, Juli; Sartika, Andry (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the description of mothers' knowledge and education regarding immunization. This study uses a quantitative descriptive research design using descriptive methods. The results of the study showed that mothers' knowledge about immunization was the highest at 69 (67.0%). The majority of mothers' education was 72 respondents (69.9%). The study concludes that mothers' knowledge and education affect immunization. Keywords: Toddlers, Immunization, Education, Knowledge